EVALUASI PROGRAM KELUARGA HARAPAN (PKH) DALAM MENINGKATKAN KUALITAS HIDUP MASYARAKAT DI DESA LAU PAK-PAK KECAMATAN TIGALINGGA - Miwanli Rajagukguk; Jonson Rajagukguk; Dimpos Manalu; Maringan Panjaitan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This research examines the Evaluation of the Family Hope Program (PKH) in Lau Pak-pak Village, Tigalingga District. The main focus of this study is the implementation of the Family Hope Program (PKH). The village government conducted group meetings and surveys of the community members who receive PKH assistance. Using a qualitative descriptive method, the results of the study show that the progress of the Evaluation of the Family Hope Program (PKH) in Lau Pak-pak Village, Tigalingga District, is considered fairly good. The implementation has been carried out properly in accordance with the procedures and mechanisms stipulated in the PKH regulations. This can be seen from the fulfillment of the elements contained in the evaluation theory according to William N. Dunn (2000: 608–610), which include: (1)Effectiveness, (2)Adequacy, (3) Equity, (4) Responsiveness, (5) Appropriateness. Based on these findings, the researcher provides several recommendations, namely: (1) In the future, an early survey should be conducted to identify eligible PKH beneficiaries.(2) Increasing the number of PKH facilitators or assistants. (3) Prioritizing the use of PKH funds for education and health purposes.